Online Indonesian Learning for Foreign Speakers (BIPA): Students' Perception at KBRI Hanoi Vietnam - Anggaira, Aria Septi (CV. Creative Tugu Pena, 2022)
Indonesian for Foreign Speakers (BIPA) is an Indonesian learning program for people whose mother tongue is not Indonesian. The BIPA program during the Covid-19 pandemic was carried out online in various parts of the world. One of the countries implementing the online BIPA program is Vietnam. There are 2 institutions that implement online BIPA programs in Vietnam, namely the Indonesian Embassy in Hanoi and the USSH Hanoi. This study aims to determine the perception of BIPA learners towards online BIPA learning, the research method used is descriptive qualitative by involving 15 Vietnamese BIPA learners. Data obtained through questionnaires related to online BIPA learning. The results of the study showed that the perception of Vietnamese BIPA learners towards online learning was very good. This is evidenced by the results of the questionnaire obtained from 15 learners who filled out the questionnaire related to online BIPA piracy. BIPA Vietnam learners still have a high enthusiasm for learning Indonesian even though it is online. Keywords: BIPA, Learner Perception, Online Indonesian Learning, Foreign Speakers Learning